The Pragmatic Aspects Ofhumor Creation: A Study On Grice's Cooperative Principles - Pradita, Intan (Journal of English and Education (JEE), 2013)
Humor is special tool of communication for its multifunction in any discourses. Its flexibility has been used by many people, of all social class, to deliver criticisms, tragedy of commons and happening issues in a funny way.This is because humor and culture are inseparable. Humor importance is undoubtedly effective to reveal the codes in cultures, politics, and education. The creation is interesting to discuss in this essay because it demands creativity, and its acceptance asks for high cognitive ability. However, a wrong perception of humor which is caused by different cultural background, and lackness of language competence is the core problem that may create missunderstanding. Through linguistics point of view, conversational principles constructed by Paul Grice is chosen as the approach of humor analysis.Keywords: pragmatics, cooperative principles, flouted maxims